Inbound marketing for Dummies : a Wiley brand - Miller, Scott Anderson (--For dummies., 2015)
Don't chase business-bring new customers to you! Outdated sales tactics have you chasing leads and fishing for new business. In today's competitive world, nobody has time for that! Inbound Marketing For Dummies is a one-stop-shop for everything you need to know about inbound marketing techniques that attract the attention of your target audience. Whether you have a small or large business, this approachable text offers insight into creating, executing, promoting, and measuring inbound marketing tactics through easy-to-follow instructions on setting up and implementing a new strategic approach.